Transparansi Penyedia Barang dan Jasa Dalam Penerapan E-Government di Kabupaten Toraja Utara - Dian Mutmainnah Arsyam; Nur Khaerah; Rudi Hardi (Universitas Muhammadiyah Gorontalo, 2016)
Implementation of e-government to achieve good governance is the procurement of goods / services government electronically or e-procurement. This research purpose to know the Transparency of Procurement of Goods and Services with LPSE in Kab. Toraja Utara. Type of research is descriptive qualitative. Research results show Transparency, procurement administration, the determination of the prospective provider in the process of opening the offer has not been transparent because only the committee and the offering owner can see it. Accountability in Procurement of Goods and Services has been effective because all data stored properly and can be accounted for. Efficient cost and budget (budget ceiling with winning bidding bid of 10-12%). Monitoring is accomplished by access in the LPSE portal to see the results of monitoring and evaluation of procurement of goods and services performed Penyelenggaraan e-government untuk mencapai good governance adalah pengadaan barang/jasa pemerintah secara elektronik atau e-procurement. Penelitan ini bertujuan untuk mengetahui Transparansi Pengadaan Barang dan Jasa dengan LPSE di Kab. Toraja Utara. Jenis penelitian adalah penelitian kualitatif. Hasil Penelitian menujukkan Transparansi, administrasi pengadaan, penetapan calon penyedia pada proses pembukaan penawaran belum transparan karena hanya panitia dan pemilik penawaran yang dapat melihatnya. Efisien biaya dan anggaran (selisi pagu anggaran dengan penawaran pemenang tender yaitu antara 10-12%). Monitoring terlaksana dengan adanya akses dalam portal LPSE melihat hasil monitoring dan evaluasi pengadaan barang dan jasa yang dilakukan